ESTIMATING ECONOMICAL COSTS FOR OPERATING AGRICULTURAL MACHINES AND EQUIPMENT DURING PLOWING OPERATIONS - & et al., Taha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was conducted in a field of Al-mahmodia Region in Baghdad , 2014 to estimate the costs of operating Massy Ferguson tractor and tillage equipment  in a clay loam soil. Three factors studied through the experiment included:- Three linear speeds for tractor were 2.85, 3.77 and 5.83 km/hr. Two types of plows included moldboard and chisel plow and two systems of plowing included one passage and orthogonal passage for each type of plows. The properties which were studied included fuel consumption, oil costs, maintenance and repair costs, labor costs per hectare. The research was done by applying the factorial experiment according to randomized complete block design with four replications and data were analyzed statistically, mean values of each treatment were compared using LSD at the 0.05 level of confidence to test significance. The results showed the following: Using chisel plow in the orthogonal pass led to increase  the rate of fuel consumption, oil costs, maintenance and repair costs and labor costs per hectare, while moldboard plow in one passage achieving decrease the fuel consumption, oil costs, maintenance and repair costs and labor costs . Increasing linear speeds of tractor from 2.85 to 3.77 and 5.83 km/hr caused decreasing in fuel consumption, oil costs, maintenance and repair costs and labor costs per hectare. Linear speed of tractor 5.83 km/hr in one passage indicated significant superiority up on 2.85 and 3.77 km/hr. in achieving decrease the rate of fuel consumption for one hectare.